Sociedade recreativa e de esportes de Ribeirão Preto: a história de um patrimônio moderno - Silva, Rosemilia Andrade Andrade da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Recreational Sports Society was founded during the coffee cycle, a period of consolidation of the economy and social and political development of Ribeirão Preto. The Club arises from the need of a place for the traditional elite families come together. The need to expand this space led to the construction of a new club on the edge of the downtown area, which in 1943 was urbanized with the construction of Nove Avenue and inaugurated a new axis of expansion of the city. The new building that opened onto the avenue was designed by early modernist architects training who worked in city-Ijair Cunha and Cassio Pinheiro Gonçalves, and has become a symbol of the modernization of the city. The research aims to rescue the cultural and architectural history of the building, considering its importance to the city before the social and economic. Thus contributing to the preservation and recognition of this heritage.

A sociedade recreativa de Esportes foi fundada durante o ciclo do café, um período de consolidação da economia e do desenvolvimento social e político de Ribeirão Preto. O Clube surge da necessidade de um local para as famílias tradicionais elitistas se reunirem. A necessidade de ampliação desse espaço levou a construção de um novo clube no limite da área central da cidade, que em 1943 foi urbanizado com a construção da Avenida Nove de Julho e inaugurou um novo eixo de expansão da cidade. O novo edifício que se abria para a avenida foi projetado pelos primeiros arquitetos de formação modernista que atuaram na cidade- Ijair Cunha e Cássio Pinheiro Gonçalves, e se tornou um símbolo da modernização da cidade. A pesquisa pretende resgatar a história cultural e arquitetônica do edifício, considerando a sua importância para a cidade diante do contexto social e econômico. Contribuindo assim, para a preservação e reconhecimento desse patrimônio.
Keywords: Sociedade recreativa; Preservation; Patrimony; Sociedade recreativa; Preservação; Patrimônio